The design and implementation of natural population cohort study Biobank: A multiple-center project cooperation with medical consortia in Southwest China - Fan, Ping; Zhang, Shu; Wang, Weiya; Yang, Zongze; Tan, Weiwei; Li, Shujun; Zhu, Chenxing; Hu, Dan; Zhou, Xinran; Tian, Zixuan; Wang, Yaxi; Liu, Fang; et al. (Frontiers in Public Health, 2022)
The West China Hospital of Sichuan University collaborated with regional medical consortia in Sichuan Province to launch a natural population cohort study (NPCS) to investigate the health status of residents and collect public health data in southwest China. To enroll 80,000 individuals over five years, the NPCS plans to recruit participants from 11 regional medical consortia. Participants are invited to visit one of 11 participating medical consortia to fill out questionnaires, receive a free health exam, and donate biospecimens upon enrolment. All participating medical facilities adhered to standard operating procedures for collecting and processing biospecimens to ensure uniformity (serum, lithium heparinized plasma, ethylene diamine tetraacetie acid plasma, and buffy coat). An estimated 2,240,000 aliquots of the sample will be stored by the end of the study. The Electronic Data Capture System, Picture Archiving and Communication System, Laboratory Information Management System, Biospecimen Quality Control System, Biobank Information Management System, and will be used to sort and classify clinical indices, imaging data, laboratory parameters, pre-analytical variables, and biospecimen information, respectively. All quality assurance and quality control procedures in the NPCS biobank adhered to the “DAIDS Guidelines for Good Clinical Laboratory Practice Standards”. Using big data analysis, the NPCS will provide an integrative approach to research risk factors and pathogenesis of major chronic or endemic diseases in Sichuan Province and provide key scientific evidence to support the formulation of health management policies in China.